PERKEMBANGAN CEKUNGAN ANTAR-BUSUR DI DAERAH MAJALENGKA-BANYUMAS: SEJARAH TEKTONIK KOMPLEKS DI WILAYAH BATAS KONVERGENSI - H. Permana; P. S. Putra; A. F. Ismiyanto; I. Setiawan; M. Hendrizan; M. M. Mukti (Jurnal Geologi dan Sumberdaya Mineral, 2011)
An intra-arc basin, Late Miocene to Pliocene in age in the region of Majalengka - Banyumas area has been an interesting theme to be discussed. The volcanoclastic sediments pathway in this basin showing different direction compare to the time equivalent sediments in the adjacent Bogor Trough. Bouguer anomaly analyses clearly imaged the E-W regional structural grains of Bogor – Bandung –Majalengka crosscut pair of NW-SE Gabon dan Pamanukan-Karangbolong strike slip fault that parallel with the postulated intra-arc basin. These NW-SE structural lineaments could be responsible for the development of sub-basins and volcanic products through splay or duplex fault or pull apart mechanism in context oblique plate subduction in Early Miocene. Study of Majenang sub-basin, whereas epiclastic rocks deposited as sediment-gravity flows and their pyroclastic, shows the significance variation, upper, middle slope to basinal plain within the deep sea submarine-fan complex of the Late Miocene-Pliocene age during the development of this basin. The source of sediment deposits was associated with calk alkalin back arc volcanic edifice that grown and separated the sub-basins and other volcanoclastic source from Southern Mountain (Old Andesite Formation). The development of this basin indicates complex history since this region is now inverted and built the mountain range. Therefore further tectonic reconstruction in this region is required for better understanding the geologic history merit further geological exploration prospect.Keywords: intra-arc basin, volcanoclastic, Bouguer anomaly, sediment-gravity flows, back arc volcanic, calk alkalin